Oxidative stress and antioxidant activity in female dogs undergoing laparoscopic and open elective ovariectomy - Kumar, Rajesh; KUMARI, ARCHANA; TIWARY, RAMESH; KUMAR, RAJESH; KANTI GUHA, SHYAMAL (The Indian Journal of Animal Sciences, 2022)
The present study was carried out to evaluate the biomarkers of oxidative stress and antioxidant activity in femaledogs undergoing laparoscopic and open elective ovariectomy at Bihar Veterinary College, Patna in 2016-17.Twenty healthy animals were randomly divided into four groups, viz. A, B, C and D consisting of 5 animals each. Theovariectomy was performed through laparoscopy in Group A and Group B. Open elective ovariectomy procedurewas used in Group C and Group D. Evaluation of surgical techniques was done on the basis of biomarkers foroxidative stress and antioxidant activity at Pre, Post and 4th day post surgery. The superoxide dismutase level onday 4th in Group B showed significant difference with highest value followed by Groups A, C and D respectively.The catalase levels on day 4th in Group B were significantly different from Groups A and D but not from Group C.The values within the groups were significantly higher on day 4th as compared to pre and post intervals of time.It can be concluded that less oxidative stress is induced during surgical procedure by laparoscopy as compared toopen laparotomy ovariectomy in canines.